Erasmus syndrome in a marble worker - S. Bello; A. Rinaldi; S. Trabucco; L. Serafino; C. Bonali; G. Lapadula (PAGEPress Publications, 2016)
Erasmus syndrome is defined as the association of silica exposure and subsequent development of systemic sclerosis. The limited number of cases reported in the literature mainly involves miners and only sporadically other professionals. We describe a case of Erasmus syndrome in a marble worker. A 68 year old man came to our observation complaining pelvic and scapular girdle pain, evening fever, intense weakness and emaciation for about 1 month. He also reported to have had Raynaud's phenomenon in his hands for the last 13 years. Also, his occupational history revealed a chronic exposure to silica dust. The patient presented pain in his shoulders and hips, moderate skin thickening and sclerosis in his hands and fingers extending proximally to his wrists. The diagnosis of systemic sclerosis was determined according to his clinical and medical history, the positivity of anti-Scl 70 antibodies, the nailfold capillaroscopy suggestive of an active scleroderma pattern and the detection of a mild restrictive pulmonary syndrome. The evaluation of the organbased complications excluded a gastroenterological and cardiovascular involvement, while the chest computed tomography (CT) detected multiple small nodules with a mantle distribution and enlarged lymph nodes with no signs of interstitial lung disease and fibrosis. Additional tests (positron emission tomography-CT, flexible bronchoscopy and broncho-alveolar lavage) excluded infectious diseases and cancer. However, given the pulmonary involvement, we performed a histological examination of the parenchyma and lymph nodes, which revealed a picture of pneumoconiosis. In the end, the occupational history and the findings from the diagnostic procedures led to the diagnosis of pulmonary silicosis. The precise definition of the pulmonary involvement was essential to the therapeutic approach to this patient.